Membedah Pentingnya Pengetahuan E-Commerce Untuk Transformasi UMKM di Desa Jarangan Kecamatan Rejoso Kabupaten Pasuruan - Akbar Maulana Muhammad Aditiya; Sugeng Pradikto (Student Research Journal, 2025)
This study examines the importance of e-commerce knowledge in supporting the transformation of MSMEs in Jarangan Village, Rejoso Subdistrict, Pasuruan Regency. Using a qualitative approach with a case study method, data were collected through in-depth interviews with 10 MSME actors, the village head, MSME coordinators, and digital facilitators. The results show that only 20% of MSMEs have utilized e-commerce platforms to market their products, achieving an average revenue increase of 40% compared to conventional methods. Meanwhile, 80% of other MSMEs still rely on traditional marketing due to limited digital literacy and confidence. These findings highlight the need for training, mentoring, and infrastructure strengthening to accelerate the digital transformation of MSMEs. E-commerce knowledge has proven to be a key catalyst in enhancing the competitiveness and sustainability of MSMEs in the digital era. With adequate support, MSMEs can maximize the potential of e-commerce to contribute significantly to the regional economy.